Patent-related actions taken in WTO members in response to the COVID-19 pandemic - Xiaoping Wu; Bassam Peter Khazin (World Trade Organization (WTO), 2020)
COVID-19, caused by SARS-Cov-2, was declared to be a pandemic by the World Health Organization on 11 March 2020. Since then, the issue of the relationship between patent protection and the development of and access to medical treatments and technologies - a longstanding and enduringly important public policy issue - has become central to the debate on the linkages between IP, innovation, access, and public health between stakeholders with divergent interests. This working paper provides an overview of the patent landscape of medical treatments and technologies related to COVID-19, and of the patent status of two investigational medical treatments: remdesivir and lopinavir/ritonavir. It then presents various patent-related actions taken by legislators, policymakers, industry sectors, and civil society organizations in WTO Members since the outbreak. Furthermore, it elaborates on patent-related policy options provided by the TRIPS Agreement, and WTO Members' national implementation and utilization of these options in their response to the COVID-19 pandemic.
Keywords: K11; K15; K30; O30; O31; O34; I18; 330; COVID-19 pandemic; patent; open innovation; patentable subject matter; repurposed medicines; exceptions and limitations; licences; government use; transition periods; LDCs; WTO; TRIPS